2018
DOI: 10.1136/bmjgh-2017-000651
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the US Food and Drug Administration registration of antiretroviral drugs on global access to HIV treatment

Abstract: BackgroundSince 2004, the US Food and Drug Administration’s (USFDA) dedicated drug review process in support of President’s Emergency Plan for AIDS Relief (PEPFAR) has made safe, effective and quality antiretrovirals (ARVs) available for millions of patients. Furthermore, the WHO and Global Fund to Fight AIDS, Tuberculosis and Malaria (Global Fund) can add the USFDA-reviewed products to their respective formularies, through a novel process of ‘one-way reliance’. We assessed the number of ARVs made available th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Just as with the WHO prequalification programme, the FDA will inspect facilities manufacturing generic drugs. [39–41] Indian generic manufacturers are significant players in the global generic drug market; for instance, India supplies more than 80% of drugs to treat AIDS in developing countries and might also play a crucial role in the fight against HCV. [42, 43] Notably, Mylan Pharma, an Indian pharmaceutical company, introduced the first generic in the Swiss market in December 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Just as with the WHO prequalification programme, the FDA will inspect facilities manufacturing generic drugs. [39–41] Indian generic manufacturers are significant players in the global generic drug market; for instance, India supplies more than 80% of drugs to treat AIDS in developing countries and might also play a crucial role in the fight against HCV. [42, 43] Notably, Mylan Pharma, an Indian pharmaceutical company, introduced the first generic in the Swiss market in December 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Continued efforts to reduce duplication of drug reviews between FDA and the WHO drug review mechanism (prequalification of medicines program), as identified by previous research, 8 are needed. As an initial step, to reduce duplication and increase timely access to ARTs in countries of greatest need, FDA and WHO have initiated a joint pilot program in which FDA will share its completed drug reviews, to determine whether this will expedite reviews of the same products by WHO’s prequalification of medicines program.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, FDA-reviewed ARTs can also be used to support HIV treatment guidelines developed by WHO and the HIV community, which includes recommendations on first-line or second-line ARTs, depending on patient needs. 8,9…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations